Seven new metal–organic frameworks assembled from semi‐rigid polycarboxylate and auxiliary N‐donor ligands: syntheses, structures and properties. Issue 6 (11th November 2020) - Zhang, Xiaoyu; Yang, Qinglin; Yun, Meng; Si, Changdai; An, Ning; Jia, Meimei; Liu, Jiacheng; Dong, Xiuyan
Abstract : Seven new metal–organic frameworks (MOFs) assembled from 3‐(3, 5‐dicarboxylphenoxy)phthalic acid (H4 L 1 ) and 4‐(3, 5‐dicarboxylphenoxy)phthalic acid (H4 L 2 ) have been synthesized under similar conditions with transition‐metal ions in the presence of auxiliary N‐donor ligands. The various structures of the MOFs have been generated by adjusting the N‐donor auxiliary ligands and the central metal ions. Their syntheses, 3D supramolecular structures, topological structures, structural comparison, fluorescence and magnetic properties are discussed in detail. Abstract : Seven new metal–organic frameworks (MOFs), namely, [Zn2 ( L 1 )(H2 O)3 ] n (1 ), [Zn2 ( L 1 )(dib)(H2 O)2 ] n (2 ), {[Zn2 ( L 1 )(4, 4′‐bipy)(H2 O)2 ]·H2 O} n (3 ), [Cd2 ( L 1 )(1, 10‐phen)] n (4 ), [Ni2 (H L 1 )(4, 4′‐bipy)(μ3 ‐OH)(μ2 ‐H2 O)] n (5 ), {[Co4 ( L 1 )(4, 4′‐bibp)3 ]·(4, 4′‐bibp)3 } n (6 ), and [Co2 ( L 2 )(4, 4′‐bibp)2 (H2 O)] n (7 ), where H4 L 1 and H4 L 2 are semi‐rigid 3‐(3, 5‐dicarboxylphenoxy)phthalic acid and 4‐(3, 5‐dicarboxylphenoxy)phthalic acid, respectively, and 4, 4′‐bipy is 4, 4′‐bipyridine, dib is 1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene, 1, 10‐phen is 1, 10‐phenanthroline and 4, 4′‐bipb is 1, 4‐bis(pyridin‐4‐yl)benzene, have been prepared under solvothermal conditions with Zn II, Cd II, Co II and Ni II ions in the presence of auxiliary N‐donor ligands. The crystal structures and photoluminescence and magnetic properties of these compounds have been investigated. Compound 1 displays a 3, 4, 6‐connected two‐dimensional (2D) topology with a Schläfli symbol of (4 2 .5)2 (4 3 .5 2 .7)(4 5 .5 6 .6 3 )2, and the 2D structure was further assembled to form a three‐dimensional (3D) framework by intermolecular O—H…O hydrogen bonds. Compound 2 features a novel 3, 3, 4‐connected structure and the point symbol is (4.10 2 )(4.6.8 4 )(6 2 .8). Compound 3 exhibits a 3, 4, 6‐connected 3‐nodal net having a 3, 4, 6 T53 type topology, with the point symbol (4.6 2 )2 (4 2 .6 4 )2 (4 2 .6 8 .8 2 .10 3 ). Compound 4 shows a 2D→3D supramolecular structure formed by π–π stacking interactions. Compound 5 possesses a 3D framework with a tfz‐d net topology. Compounds 6 and 7 are constructed from the same auxiliary ligand and metal salt at the same temperature, but with different main ligands and exhibiting different topologies. Compound 6 presents a 3D 4, 6‐connected topological network with a Schläfli symbol of (3.4 4 .6)(3 2 .4 4 .5 6 .6 3 ), while compound 7 has a 3D topological network with a Schläfli symbol of (4 12 .6 16 ). Magnetic analyses indicate that compounds 5 and 7 show weak antiferromagnetic interactions.